THE IMPACT OF USER-GENERATED CONTENT ON PURCHASING INTENTION OF TRAVEL PRODUCT (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2023)
The upsurge of social media has permitted one  and all to share their purchase and consuming  experiences, including the usage of travel  products. The study’s objective is to observe if a  user’s attitude toward UGC and UGC impacts  their purchase intention for a travel product.  Questionnaires were distributed online to 233  people over 18 who had seen at least one travel  product review. The data were analyzed using  factor analysis and regressions. The data show  that attitudes and perceived credibility impact  purchase intentions, but user activities do not  only influence purchase intentions for travel  products. UGC often contains information  and suggestions, and strategies for using  travel products. Findings from this study are  projected to extend the literature on UGC and  give assistances to marketers and online tour  operators.
Keywords: User Generated Content (UGC); attitudes; perceived credibility; purchase intentions